Imaging features in incident radiographic patellofemoral osteoarthritis: the Beijing Shunyi osteoarthritis (BJS) study - Qiu, Yudian (BMC Musculoskelet Disord, 2019)
BACKGROUND: The present study aims to describe the imaging features in incident radiographic patellofemoral osteoarthritis (RPFOA) population in a Chinese suburban area. METHODS: The Beijing Shunyi osteoarthritis (BJS) study was a population-based, longitudinal and prospective study. Residents were recruited by randomized cluster sampling in 2014 and were followed 3 years later. Home interviews and clinical examinations were performed; weight-bearing posterior-anterior semi-flexed (45-degree) views of the tibiofemoral (TF) joints and skyline (45-degree) views of the patellofemoral (PF) joints were included. For each batch of study films (n = 100), 20 films from the year 2014 and 20 previously read PF radiographs were fed back to test inter−/intra-reader repeatability. The imaging features of incident RPFOA were analyzed. Narrative statistics, independent-sample t-tests, and nonparametric tests were performed. RESULTS: A total of 1295 participants (2590 knees) were recruited at baseline in 2014, and 967 (74.7%) residents were followed in 2017. Of all the knees (n = 1537) without RPFOA at baseline, 139 knees (13.3%) across 119 people developed incident RPFOA. Compared with the whole population, age (p = 0.031), body mass index (BMI, p = 0.042), and incidence of knee pain symptoms (p < 0.01) were significantly different in the incident RPFOA population, while range of motion (ROM, p = 0.052) and gender (0/1, p = 0.203) showed no significance. In the incident population, the changes of each imaging indicator grade were evaluated—lateral patellofemoral osteophyte (LPOST, increased by 1.02), medial patellofemoral osteophyte (MPOST, increased by 0.49), lateral joint space narrowing (LJSN, increased by 0.30), medial joint space narrowing (MJSN, increased by 0.06); indicator grade progress decreases, respectively. The progress of LPOST was the fastest among the four indicators (p < 0.01). CONCLUSIONS: In this population-based longitudinal study, among the incident RPFOA population, the imaging indicators show that marginal patellofemoral osteophyte is more pronounced than patellofemoral joint space narrowing. LPOST is the fastest-progressing indicator among all the radiographic features, which is also the most common imaging manifestation of RPFOA. In the incident RPFOA population, the proportion of elders, women, higher-BMI individuals, and people suffering knee pain is more than the normal population.